The Reality of Using International Marketing Strategies in Good Food Industries Company: A Case Study (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of the research is to assess the reality of the application of international marketing strategies (international pricing, international promotion, international product, international distribution) at Jude Food Industries Company. The research adopted the case study curriculum, which is a research method concerned with a phenomenon or a specific event in depth and comprehensively, and the researcher conducted a set of interviews with administrators responsible for the Joud Food Industries Company, and their number reached (35) administrators, where the questionnaire was distributed to the study tool to them, in order to evaluate the reality of using international marketing strategies.The search results revealed that the company applies the international pricing strategy to a moderate degree by relying on the cost as a standard for pricing its services, and the international promotion strategy applies high by relying on the advertisement on internet sites to promote its services in international markets, and the international product strategy is applied high by developing its services including The international market requirements are compatible, the adoption of a quality certificate, and the international distribution strategy applies to a moderate degree through the use of electronic networks to exchange information with suppliers.